2011
DOI: 10.1590/s0080-62342011000800018
|View full text |Cite
|
Sign up to set email alerts
|

Possibilidades do WHOQOL-bref para a promoção da saúde na estratégia saúde da família

Abstract: resumoA ampliação das ações de promoção da saúde na Estratégia Saúde da Família pode contribuir para a construção da integralidade, mas, ainda persistem lacunas de tecnologias para instrumentalizar os profissionais a analisarem os potenciais de saúde da população. O objetivo deste estudo é sintetizar as contribuições do WHOQOL-bref para instrumentalizar ações de promoção da saúde na Estratégia Saúde da Família. Foi realizada uma metassíntese qualitativa a partir de pesquisas realizadas pelo grupo Modelos tecno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 10 publications
0
4
1
15
Order By: Relevance
“…The average of the scores of the four domains in this study was lower for the Physical, like the one found in a study carried out to synthesize the contributions of the WHOQOL-bref to instrumentalize health promotion actions in the Family Health Strategy 18 . Different scores were found in a study that examined the performance of the WHOQOL-bref as an integrated instrument, with the highest score being found in Brazil in the Physical domain and the lowest in the Environment 19 .…”
Section: Discussioncontrasting
confidence: 39%
“…The average of the scores of the four domains in this study was lower for the Physical, like the one found in a study carried out to synthesize the contributions of the WHOQOL-bref to instrumentalize health promotion actions in the Family Health Strategy 18 . Different scores were found in a study that examined the performance of the WHOQOL-bref as an integrated instrument, with the highest score being found in Brazil in the Physical domain and the lowest in the Environment 19 .…”
Section: Discussioncontrasting
confidence: 39%
“…Here one returns to one of the principles of PHC -the promotion of health. However, as has been affirmed by Chiesa et al 35 , there is a difficulty in the operationalization of actions which promote health services, one of the motives being the lack of understanding on the part of the professional personnel with regard to the concept as they often reduce it to the prevention of diseases, as has been found in this research project.…”
Section: ] "(Dsc-s6)mentioning
confidence: 66%
“…Portanto, é relevante estimular o olhar dos profissionais no sentido de encorajar as potencialidades de saúde dos indivíduos e grupos. O que significa não se restringir aos tratamentos das patologias e situações manifestados, mas sim ampliar projetos terapêuticos que reconheçam a qualidade de vida como meta de saúde a ser alcançada (CHIESA et al, 2011).…”
Section: Acolhimento De Enfermagem à Paciente Com Endometrioseunclassified